Association between 1‐year patient outcomes and opioid‐prescribing group of emergency department clinicians: A cohort study with Army active‐duty soldiers. (25th August 2021) - Bauer, Mark R.; Larson, Mary Jo; Moresco, Natalie; Huntington, Nick; Walker, Regine; Richard, Patrick
Abstract: Objective: The objective was to examine the association between clinicians' opioid prescribing group and patients' outcomes among patients treated in the emergency department (ED). Methods: This was a retrospective cohort study. The setting was the EDs of the U.S. Military Health System (MHS). Patients were 181, 557 Army active‐duty opioid‐naïve (no fill in past 180 days) patients with an index encounter to the ED between October 2010 and September 2016. Exposure was patients classified by opioid prescribing tier of the treating ED clinician: top, middle, or bottom third relative to the clinician's peers in the same ED. Follow‐up measurement was from 31 to 365 days after the index encounter. The primary outcome was long‐term opioid prescriptions (LTOPs) defined as 180 (or more) days' supply within the follow‐up window. We also computed the total morphine milligram equivalents (MME) and total opioid days' supply. Secondary measures were any repeat ED encounter, any hospitalization, any sick leave, and any military‐duty restriction. Results: We found a 2.5‐fold variation in opioid prescribing rates among clinicians in the same MHS ED. Controlling for sample demographics, reason for encounter, and military background, in multivariate analyses the odds of receiving a 180‐day opioid supply during follow‐up were 1.19 (95% confidence interval [CI] = 1.01 to 1.40, p < 0.05) for the top opioid exposure group and 1.37 (95% CI = 1.19 to 1.57, p < 0.001) for the middle opioid exposure group compared to the bottom exposure group, and there were significant increases in total opioid days' supply and total MME. There were no differences in secondary outcome measures. Conclusion: In a relatively healthy sample of Army soldiers, variation in opioid exposure defined by clinician's prescribing history was associated with increased odds of LTOP and increase in opioid volume, but not in functional outcomes.